An Analysis Of Language Style In Battleship Movie - Hia, Leli Arlinawati; Sembiring, Rony Arahta; Sihite, Jubil Ezer (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This study examines the use of language styles in the Battleshipmovie based on Martin Joos' (1967) theory that classifies language styles into five categories: frozen, formal, casual , consultative, and intimate. This study aims to identify the types of language styles in the movie dialogue and understand their functions in supporting social relationships between characters and storyline development. The research uses a descriptive qualitative method with the data source in the form of Battleship movie dialog transcripts, which lasted 2 hours and 11 minutes. The data was collected through direct observation by watching the movie, recording the dialog, and classifying it based on the five categories of language style according to Martin Joos' theory. Analysis was conducted through tagging, coding, and interpreting the data to identify patterns, frequency, and linguistic characteristics in the dialogs. The findings show that of the 100 dialogues analyzed, casual language style dominates with a frequency of 50% of the total data. This language style reflects an intimate and relaxed atmosphere among the characters, relevant to friendly relationships and cooperation in the face of conflict. Formal style appears at 29%, consultative 12%, intimate 6%, and frozen only 3%. The dominance of casual style reflects the more informal context of communication in this movie, especially among friends and coworkers. The use of language styles in Battleship movie not only reflects the dynamics of social relationships between characters but also plays a role in building the atmosphere of the narrative and supporting the audience's understanding of the conflict in the story. This research contributes to linguistic studies, particularly in understanding stylistic variations in film media, as well as providing references for further research on stylistics in other media such as television series or video games.